Coding-Aware Routing with Shortest Path Based Backpressure Scheme - Yue Hai, Xiaolei Wang, Long Hai (Forest Chemicals Review, 2022)
Coding-aware routing is an effective method to effectively improve the network coding gain and obtain the maximum network transmission capacity. Different from the traditional coding-aware method, this paper proposes a dynamic coding-aware routing method by integrating network coding-awareness, shortest hop strategy and back-pressure routing. This method gets rid of the dependence of traditional code-aware routing on network topology and spatial distribution of data flows. Taking advantage of the inspiration of load balancing, we realize the dynamic integration of coding perception and data routing by utilizing the data backlog pressure between nodes as the driver of data. The simulation results show that the routing method of this paper can effectively improve the network transmission capacity and increase the network throughput in a grid wireless network.